Earthworm communities in long-term no-tillage systems and secondary forest fragments in Paraná, Southern Brazil - Dudas, Rafaela T.; Demetrio, Wilian C.; Maia, Liliane S.; Sátiro, José N.o.; Silva, Karlo A.; Nicola, Vitoria B.; Kille, Peter; Oliveira, Cintía M.r.; Afonso, Rita O.; Russell, Georgina; Ferreira, Nuno G. C.; Cunha, Luis; et al. (Zootaxa, 2023)
The area destined for agricultural production in Paraná state in Brazil is ~6 million hectares, of which 79% are under no-tillage systems (NTS) that can positively affect earthworm populations. Furthermore, earthworm abundance and richness can be valuable soil quality. This study assessed earthworm communities in long-term no-tillage sites (NTS) and nearby secondary Atlantic Forest (SF) fragments. Sampling was performed in June 2018 and May 2019 using the quantitative Tropical Soil Biology and Fertility handsorting method (ISO-TSBF), complemented by qualitative sampling in three municipalities: Faxinal, Mauá da Serra and Palmeira, in NTS and SF. Eleven earthworm species, belonging to five families (Benhamiidae, Glossoscolecidae, Megascolecidae, Ocnerodrilidae, and Rhinodrilidae) were found along with seven native species (Glossoscolex sp.22, Glossoscolex sp.23, Fimoscolex sp.21, Fimoscolex sp.24, Fimoscolex sp.42, Andiorrhinus duseni and Urobenus brasiliensis) and four exotic or cosmopolitan species (Dichogaster gracilis, Amynthas gracilis, Metaphire californica and Pontoscolex corethrurus). The cosmopolitan P. corethrurus dominated Faxinal and Mauá da Serra, while in Palmeira Fimoscolex and Glossoscolex were the most abundant. Six species belonging to Glossoscolex and Fimoscolex were new to science and must be described. Overall, 239 individuals were found. In 2018 126 individuals were found (76 in NTS and 50 in SF) and in 2019, only 112 individuals were found (45 in NTS and 67 in SF). The highest earthworm abundance was in Faxinal (123 individuals), with 76 individuals in NTS and 47 in SF. In Mauá da Serra the same pattern was observed (SF>NTS), while in Palmeira in overall, fewer individuals (38) were collected (24 in NTS and 14 in SF). The NTS at Faxinal and SF Mauá da Serra in 2019 had only/more exotic/cosmopolitan species, while at the other dates and sites >50% of the specimens sampled were native species. Overall, forests had more native species than exotics: in 2018, natives represented > 75% of all specimens, but in 2019 both Faxinal and Mauá da Serra had more exotic species (> 65%), while at Palmeira, they represented 50% of the individuals. Earthworm total biomass for forest sites was higher in Faxinal (3.2 g) and NTS in Mauá da Serra (1.7 g) in 2019. Overall, the total biomass was higher in SF sites than NTS. Using a classification available for earthworm populations in no-tillage systems, all three sites were considered to have poor quality in terms of abundance (ind m-2), while for species richness, they were considered to have moderate (Faxinal and Mauá da Serra) and good quality (Palmeira).